1995
DOI: 10.1111/j.2042-7158.1995.tb06714.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Polystyrene Microspheres from the Gastrointestinal Tract to the Circulation after Oral Administration in the Rat

Abstract: Factors relating to the transfer of latex microspheres of 0.87 micron mean diameter from the gastrointestinal tract (GIT) to the circulation have been investigated. The rapidity of appearance and the number of particles increased when the volume of water used as a suspending vehicle was increased. This was probably due to barrier cell integrity being compromised so that the movement of particles across the enterocytes would be enhanced. Particles were swept into these channels by the waterflow. The tonicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Much of the observed ability of these systems for the effective generation of immune responses may be due to the observed increase in uptake of these carrier systems via mucosal routes of administration. Accumulation in the systemic compartment (specifically in circulating blood) has been demonstrated following latex microsphere application to the nose in mice and following oral administration into the gastrointestinal tract in rats (Eyles et al, 1995). Comparable results have been shown following oral administration of poly(lactic acic) microspheres in rats (Eyles et al, 1997) and similar observations have been made in other studies that have examined biodistribution following mucosal delivery of polymer based delivery systems.…”
mentioning
confidence: 69%
“…Much of the observed ability of these systems for the effective generation of immune responses may be due to the observed increase in uptake of these carrier systems via mucosal routes of administration. Accumulation in the systemic compartment (specifically in circulating blood) has been demonstrated following latex microsphere application to the nose in mice and following oral administration into the gastrointestinal tract in rats (Eyles et al, 1995). Comparable results have been shown following oral administration of poly(lactic acic) microspheres in rats (Eyles et al, 1997) and similar observations have been made in other studies that have examined biodistribution following mucosal delivery of polymer based delivery systems.…”
mentioning
confidence: 69%
“…Currently, there are contrasting data available describing the extent of particle uptake following repeated administration to the same animal. While some researchers have reported high levels of uptake, 9,11 low levels of uptake have been reported by others. 3,4,12,13 The preferred methodology to quantify total particle uptake remains unknown, and many of the studies reviewed here were not designed with this objective in mind.…”
mentioning
confidence: 82%
“…For example, it has been reported that identical numbers of 870 nm particles have been administered to rat stomach by gavage at 0.1 mL and 0.5 mL volumes. The administration of these large nanoparticles in the higher volume of water resulted in five times the quantity of particles found in the systemic circulation 15 min post dosing and was suspected to be due to compromised barrier function [87]. Clearly extreme care must be taken as error due to dilution may be perceived in significantly improved bioavailability.…”
Section: Variance In Animal Models and Difference In Normal Human Gt mentioning
confidence: 98%